Design Concepts of Virus-Like Particle-Based HIV-1 Vaccines - Chen, Chun-Wei; Saubi, Narcís; Joseph-Munné, Joan (Frontiers in Immunology, 2020)
Prophylactic vaccines remain the best approach for controlling the human immunodeficiency virus-1 (HIV-1) transmission. Despite the limited efficacy of the RV144 trial in Thailand, there is still no vaccine candidate that has been proven successful. Consequently, great efforts have been made to improve HIV-1 antigens design and discover delivery platforms for optimal immune elicitation. Owing to immunogenic, structural and functional diversity, virus-like particles (VLPs) could act as efficient vaccine carriers to display HIV-1 immunogens and provide a variety of HIV-1 vaccine development strategies as well as prime-boost regimes. Here, we describe VLP-based HIV-1 vaccine candidates that have been enrolled in HIV-1 clinical trials and summarize current advances and challenges according to preclinical results obtained from five distinct strategies. This mini-review provides multiple perspectives to help in developing new generations of VLP-based HIV-1 vaccine candidates with better capacity to elicit specific anti-HIV immune responses.